1991
DOI: 10.1113/jphysiol.1991.sp018393
|View full text |Cite
|
Sign up to set email alerts
|

Task‐dependent changes in the responses to low‐threshold cutaneous afferent volleys in the human lower limb.

Abstract: SUMMARY1. In seven human subjects who were standing without support the sural nerves were stimulated electrically using trains of non-painful stimuli (five pulses at 300 Hz), designed to activate afferents from cutaneous mechanoreceptors. The reflex effects of the stimulus train on different muscles of the ipsilateral and contralateral legs were sought in post-stimulus averages of rectified EMG. Changes in the pattern of reflex influence were investigated when the subjects maintained different postures.2. Clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(94 citation statements)
references
References 24 publications
6
87
0
Order By: Relevance
“…5) the amplitude of the subtracted responses were often larger than fourfold the maximum background activation encountered during gait. In control subjects the contralateral medium-latency cutaneous reflex responses are normally smaller than the corresponding ipsilateral responses during gait (Van Wezel et al 1997) and during nonlocomotor tasks (Burke et al 1991). Furthermore, in our laboratory such high amplitudes of contralateral reflex responses were never observed in healthy subjects during normal gait (Duysens et al 1990(Duysens et al , 1991Van Wezel et al 1997).…”
Section: Phase-dependent Increase In Cbf In Some Pd Patientsmentioning
confidence: 81%
See 1 more Smart Citation
“…5) the amplitude of the subtracted responses were often larger than fourfold the maximum background activation encountered during gait. In control subjects the contralateral medium-latency cutaneous reflex responses are normally smaller than the corresponding ipsilateral responses during gait (Van Wezel et al 1997) and during nonlocomotor tasks (Burke et al 1991). Furthermore, in our laboratory such high amplitudes of contralateral reflex responses were never observed in healthy subjects during normal gait (Duysens et al 1990(Duysens et al , 1991Van Wezel et al 1997).…”
Section: Phase-dependent Increase In Cbf In Some Pd Patientsmentioning
confidence: 81%
“…For other reflexes some abnormalities were reported as well. For example, abnormalities in postural reflexes have been observed (Beckley et al 1991;Bloem et al 1995;Carpenter et al 2004;Chong et al 2000;Dietz et al 1988Dietz et al , 1995Dimitrova et al 2004;Schieppati and Nardone 1991). However, these abnormalities did not seem to involve the basic synergies (Dimitrova et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Electrical stimulation of populations of cutaneous afferents innervating the sole and toes has been shown to exert both excitatory and inhibitory reflex effects on on-going voluntary contractions of muscles acting about the ankle (Aniss et al 1992;Gibbs et al 1995); reflex modulation has also been observed in remote muscles (Gibbs et al 1995;Zehr et al 2001). However, these reflex effects are not immutable-they can be modulated by the gait cycle (De Serres et al 1995;Duysens et al 1990;Haridas and Zehr 2003;Yang and Stein 1990) and postural task (Burke et al 1991). The pathways involved in the reflex coupling between cutaneous mechanoreceptors and muscles of the lower limb are proposed to include a range of pathways, from oligosynaptic spinal pathways (Aniss et al 1992) to transcortical pathways (Christensen et al 1999;Nielsen et al 1997).…”
Section: Introductionmentioning
confidence: 96%
“…Reflex modulation of lower limb muscles by cutaneous afferents had been proposed by Sherrington (1910), and more recent work has highlighted the important role of such reflexes in gait (Zehr et al 1997(Zehr et al , 1998 and posture (Day and Cole 2002) and emphasized that the reflexes are not simple "limb flexion"/withdrawal reflexes (Burke et al 1991). In fact, efforts are already underway to attempt to augment cutaneous feedback in an effort to increase postural control (Priplata et al 2003).…”
Section: Functional Implicationsmentioning
confidence: 99%
See 1 more Smart Citation